Evaluating the Frequency of Clinical and Microscopic Views of Basal Cell Carcinoma in a 10-Year Period - KH Abdal; J Salehinejad; S Mostafazadeh (Islamic Azad University, 2016)
Background and aim: Basal Cell Carcinoma (BCC) is the most common skin neoplasm and the most common type of cancer. Since the incidence of injury is taken into consideration in the pathologic diagnosis, the study of clinical and microscopic views of BCC is of particular importance. The present study aimed at determining the frequency of clinical and microscopic views of BCC in a 10-year period in Ilam province. Materials and Methods: This study is descriptive. The study population consisted of all the subjects with BCC in the head and neck area referring to the pathology department of Imam Khomeini hospital in Ilam province in a 10-year period. The data were entered into SPSS 19 software and were analyzed using descriptive statistical methods and Chi-Square test. Results: In the present study, 205 patients were diagnosed with BCC. The maximum and minimum frequency rates of the lesion were detected in the frontal area (9.23%) and neck (8.7%), respectively. The maximum frequency was related to the nodular type (57.1%), while the pigmented variant showed the lowest rate (8.3%). Among the evaluated microscopic variants, maximum views were related to the solid-cystic type (57.1%), while minimum views were related to the pigmented variant (37.3%). There was no significant correlation between the location of the lesion in males and females (p=0.14) or between the location of the lesion and age (p=0.16). Conclusion: The results of this study showed that the nodular type was the most common clinical variant of BCC, while the least common type was the pigmented variant. The most common histological type was the solid-cystic type, while the pigmented variant was the least common type.